Tasting the Kingdom: Wine-Drinking and Audience Inference in Mark 15.36. (June 2018) - Whitenton, Michael R.
This article explores ancient and modern reflection on inference generation and its implications for potential audience inferences concerning the Markan Jesus and whether he drinks the wine the bystander offers him while crucified (15.36). By examining this logical possibility from the perspective of hearing, rather than silent reading, this article sets forth previously underappreciated evidence that Mark's narrative is intentionally vague at this point, prompting listeners to decide the matter for themselves. Moreover, I argue that the flow and rhetoric of the narrative both suggest that hearers were meant to infer that Jesus does indeed drink – and in so doing enjoy an ironic foretaste of Mark's vision for the kingdom of God.